SATIRICAL ELEMENTS IN THE ALBUM ”TO PIMP A BUTTERFLY” BY KENDRICK LAMAR - Anugrah, Muh. Andre; Nur, Riola Haya (Journal of English Literature and Linguistic Studies, 2025)
Contemporary hip-hop has established itself as one of the most powerful forms of social commentary in popular music, yet limited scholarly attention has been paid to how satirical techniques specifically function within contemporary albums as both artistic devices and tools for social critique. This study examines the satirical elements in Kendrick Lamar's 2015 album "To Pimp a Butterfly" and analyzes how these elements are constructed through the interplay of musical composition, lyrical content, and cultural context. Using an integrated theoretical framework combining Linda Hutcheon's satirical theory and Philip Tagg's song analysis theory, this qualitative research employs thematic analysis to identify and categorize satirical techniques across the album's content. The analysis reveals six distinct types of satirical elements: irony and contradiction, personification and allegorical satire, exaggeration and hyperbole, parody and cultural mimicry, temporal satire and anachronism, and meta-satirical self-critique. Among these, irony and contradiction emerged as the most prevalent technique, functioning as the foundation of Lamar's critical approach to exposing contradictions inherent in American society. The study demonstrates how satirical meaning in contemporary hip-hop emerges from complex multi-modal expression rather than from lyrical content alone, contributing to understanding of how popular music functions as a vehicle for sophisticated social critique while maintaining commercial viability and artistic authenticity.